Efisiensi Teknis Usahatani Kentang di Kabupaten Gowa Sulawesi Selatan - Ahsanah Mukarromah Arifin; Anna Fariyanti; Netti Tinaprilla (Forum Agribisnis, 2021)
One of the ways to increase production was increasing technical efficiency. The purpose of this research was to analyze technical efficiency and factors that affected technical efficiency in Tinggimoncong District, Gowa Regency, South Sulawesi. This research used purposive sampling with 50 potatoes farmers. This study used Data Envelopment Analysis (DEA) approach and Tobit regression for data analysis. The result of the study showed that there are 23 farmers of the respondents stated to be efficient or about 46 per cent of the total respondents studied. Factors that significantly influence the technical efficiency of potato farming were education and income outside of farming.